Emotions in the mathematics knowledge’s desertion - Jiménez Espinosa,, Alfonso; Pérez Martínez, Ana Mercedes (Universidad Pedagógica y Tecnológica de Colombia, 2010)
The natural wearing out of students has become one of the most worrying problems for universities, but underlies another, dropping out of mathematical knowledge, which is one of the causes of the first. The mathematics learning occurs mainly in class and there is where the concept interstructuring, the network of relationships, emotions, attitudes and beliefs among the known and the new, acquire a meaning and where the student learns. This research investigates the relationship between emotions and mathematics’ learning in students at the Geological Engineering Program of the UPTC. Through the case study and the “Theoretically informed” approach is shown the intricate relationship between emotionality and the construction of mathematical structures. Weconclude that emotions, especially negative ones arise because of the inability to achieve a cognitive balance, leading the student to change his action domain, preventing the construction of mathematical knowledge. It is emphasized that these negative emotions have different origin, especially those generated by beliefs about mathematics and the unfortunate attitude of teachers.